2022
DOI: 10.1002/adhm.202200055
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Designing Electroconductive Biomaterials for Cardiac Tissue Engineering

Abstract: Implantable cardiac patches and injectable hydrogels are among the most promising therapies for cardiac tissue regeneration following myocardial infarction. Incorporating electrical conductivity into these patches and hydrogels is found to be an efficient method to improve cardiac tissue function. Conductive nanomaterials such as carbon nanotube, graphene oxide, gold nanorod, as well as conductive polymers such as polyaniline, polypyrrole, and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate are appealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 173 publications
0
18
0
Order By: Relevance
“…[ 5 ] Notably, electrically conductive biohybrid systems provide an environment to facilitate the propagation of intercellular electrical signals. [ 6 ] Different electroconductive materials, including nanoparticles, nanorods, nanowires, carbon nanotubes, and polymers have been used in tissue engineering applications. [ 7 ] We have previously shown that introducing electroconductive materials facilitates intercellular communications, enhances cardiomyocyte maturation, and improves the beating properties of engineered cardiac tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Notably, electrically conductive biohybrid systems provide an environment to facilitate the propagation of intercellular electrical signals. [ 6 ] Different electroconductive materials, including nanoparticles, nanorods, nanowires, carbon nanotubes, and polymers have been used in tissue engineering applications. [ 7 ] We have previously shown that introducing electroconductive materials facilitates intercellular communications, enhances cardiomyocyte maturation, and improves the beating properties of engineered cardiac tissues.…”
Section: Introductionmentioning
confidence: 99%
“…They are supposed to be superior for the fabrication of electronic devices in contrast to inorganic materials in view of their flexibility, stretchability, and biocompatibility features. [6][7][8][9][10][11][12] Piezoelectricity-based flexible sensors have numerous advantages over the existing technologies such as photoplethysmography (PPG) and electrocardiogram (ECG) as piezoelectricity-based sensors are self-powered, easy to fabricate, cost-effective, confirmable with the skin, and it provides direct measurements of the physiological events with greater sensitivity.Among the several piezoelectric polymers, odd-nylons (e.g., nylon-11) are treated as one of the best suitable materials for Cardiovascular diseases are found as one of the major cause of deaths globally, these can be reduced substantially if early-stage detection and intervention is possible. Regular monitoring of the arterial pulse is one of the possible solutions, however, existing technologies have put limitations, due instability in continuous monitoring, lack of information in real-time recording of cardiovascular parameters and bulky instruments.…”
mentioning
confidence: 99%
“…They are supposed to be superior for the fabrication of electronic devices in contrast to inorganic materials in view of their flexibility, stretchability, and biocompatibility features. [6][7][8][9][10][11][12] Piezoelectricity-based flexible sensors have numerous advantages over the existing technologies such as photoplethysmography (PPG) and electrocardiogram (ECG) as piezoelectricity-based sensors are self-powered, easy to fabricate, cost-effective, confirmable with the skin, and it provides direct measurements of the physiological events with greater sensitivity.…”
mentioning
confidence: 99%
“…Nanotechnologies, encompassing focused administration of drugs, heat treatment, light-based assays, light-induced therapy, and tissue engineering, have been considered to be encouraging methodologies to tackle the drawbacks of existing techniques. 2,3 These advancements hold promise in providing potential solutions to surmount these obstacles.…”
Section: Introductionmentioning
confidence: 99%